Strategi Pembelajaran Melalui Model Card Sort dan The Power of Two and Four di Madrasah Ibtidaiyah Az-Zainiyah II Grinting Paiton Probolinggo - BZ, Zakiyah; Azizah, Rizka Nur (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This research was carried out with the aim of improving student learning outcomes by discussing and helping students to be confident in presenting the results of their discussions in front of other students. This research is classroom action research in which the object of this research is 12 grade 5 students at MI Az-Zainiyah II, which includes 4 stages: 1. Planning 2. Implementation 3. Observation 4. Reflection. This research data was taken from the observation process, interviews with the homeroom teacher and grade 5 students, documentation, and practice of applying the Card Sort and The Power Of Two And Four learning models. Which is the result of this research, students learn more effectively and happily because in the Card Sort model which uses cards which are a book of concepts like a game so that students are interested in choosing challenges or questions on the cards, and by collaborating with The Power Of Two And Four model Students can develop what they think in group discussions and students train their self-confident courage to appear in front and present the results they have discussed. The conclusion of this research is to apply the Cart Sort and The Power of Two and Four Learning Model to science subjects with light energy material for grade 5 students at MI Az-Zainiyah II Grinting Paiton Probolinggo.